2019
DOI: 10.1042/bsr20181882
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-625 inhibits cell invasion and epithelial–mesenchymal transition by targeting SOX4 in laryngeal squamous cell carcinoma

Abstract: Introduction: Laryngeal squamous cell carcinoma (LSCC) is a highly aggressive malignant cancer, but the molecular mechanisms underlying its development and progression remain largely elusive. The purpose of the present study is to investigate the expression profile and functional role of microRNA-625 (miR-625) in LSCC.Materials and methods: LSCC tissues and adjacent normal tissues were collected from 86 LSCC patients. The expression levels of miR-625 and SOX4 mRNA in tissues and cells were detected by RT-qPCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 18 publications
1
31
0
Order By: Relevance
“…Moreover, EMT also helps promote hepatic fibrosis by providing a pre-metastatic microenvironment [ 35 ]. A plethora of studies confirms the influential role of miRNAs in EMT process [ 36 , 37 ]. In the current study, miR-296-5p showed a positive correlation with E-cadherin level, and both in vitro and in vivo experiments also demonstrated that miR-296-5p could reverse the EMT phenotype and metastatic capability in HCC cells.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, EMT also helps promote hepatic fibrosis by providing a pre-metastatic microenvironment [ 35 ]. A plethora of studies confirms the influential role of miRNAs in EMT process [ 36 , 37 ]. In the current study, miR-296-5p showed a positive correlation with E-cadherin level, and both in vitro and in vivo experiments also demonstrated that miR-296-5p could reverse the EMT phenotype and metastatic capability in HCC cells.…”
Section: Discussionmentioning
confidence: 90%
“…33 As for CCRCC, it was revealed that EMT was attenuated by miR-138 in CCRCC cells, indicating the tumor suppression function of miR-138. 34 on the contrary, IL-6 induces EMT and stimulates metastasis in CCRCC. 35 Furthermore, Jiang J et al Has reported that increased expression of miR-200c inhibits the cell viability and EMT of clear cell renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 92%
“…A number of recent studies have identified a variety of deregulated miRNAs in ccRCC, including miR-224 (27), miR-502 (28), miR-543 (18) and miR-645 (29). miRNAs are involved in several biological and pathological processes, including ccRCC occurrence and development (30)(31)(32). Previous studies have also identified several deregulated miRNAs in ccRCC, whereby oncogenic miRNAs are upregulated and tumor suppressor miRNAs are downregulated (17,33).…”
Section: Discussionmentioning
confidence: 99%